A modular toolset of phiC31-based fluorescent protein tagging vectors for Drosophila. Issue 1 (2nd October 2019) - Luo, Jun; Shen, Pingping; Chen, Jiong
ABSTRACT: The Drosophila transgenic technology and fluorescent protein fusions are powerful tools to analyze protein expression patterns, subcellular localization and protein dynamics. Recently, the Drosophila transgenic technology has been improved by the highly efficient phiC31 site-specific integration system. Many new and improved fluorescent proteins with desirable advantages have been developed. However, the phiC31 system and the newly developed fluorescent proteins have not been systematically applied in Drosophila transgenic vectors. Here, we have constructed a modular toolset of C-terminal fluorescent protein fusion vectors based on phiC31 site-specific integration system for the generation of transgenic Drosophila lines. These cloning vectors contain a variety of fluorescent tags, including blue, cyan, green or red fluorescent proteins, photoactivatable or photoswitchable fluorescent proteins, fluorescent timers, photosensitizers and bimolecular fluorescence complementation tags. These vectors provide a range of transcriptional regulation options including UAST, UASP, UASC, LexAop, QUAS, Ubi, αTub67C and αTub84B promoters, and two screening marker options including white and vermilion gene. The vectors have been tested in vivo and can produce fluorescent chimeric proteins that are functional.